MEMORY, VIOLENCE, RELIGION AND IMMORALITY IN POSTCOLONIAL DISCOURSE: RE-READING ISIDORE OKPEWHO’S THE LAST DUTY - Kalu Obasi , Kalu; Ukam , Edadi Ilem (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
Memory, which is the art of storage of pieces of information and regurgitating them for use by remembrance, is useful tool in literary tradition. Memory weaves up the word, the incident and the action in any work of art. Literature thus is seen as metonymy which word are put for thought. Memory graduates into the words which is language and becomes personalized in action. This paper attempts to establish the relationship that exists among memory, violence, religious and immorality in Okpewho’s The Last Duty (1976), using the view point of post- colonialism. It attempts to unravel the structural pattern which the writer of the novel adopts to brace up the actions and events that happen in the novel in view of a master-servant relationship. The novel is made up of three parts each featuring the characters themselves in action, each narrating their own case or part. The writer uses the memory of the war event to describe the violence and immorality that exist in society virtually enshrined in religion and the fear of God. The actions of Major Ali blend with Major Bello. The activities of the military align with the war time, while Chief Toje’s actions are in tandem with his accomplices. Odibo, Oghenovo, Oshevire and Aku are merged together but Oghenovo exhibits a child’s innocence throughout the novel. Domination gives effect in violence. When what ought to be done is not done, violence ensues. The writer captures this scenario of omission and neglect from the beginning to the end of the novel. The war (Biafran/Nigerian war is caused by domination, the fight and consequent death of the private soldier is domination; the hatred and implication of Oshevire by Chief Toje is engendered by dominating in as much as the fight and violent acts of Odibo and Chief Toje over Aku, Oshevire’s wife. Each of these establishes a post-colonial relation. The author uses this novel and the events in it to give a summary picture of what transpired at the war time.